In vitro validation of flow measurements in an aortic nitinol stent graft by velocity-encoded MRI - Rengier, Fabian; Delles, Michael; Weber, Tim; Böckler, Dittmar; Ley, Sebastian; Kauczor, Hans-Ulrich; Tengg-Kobligk, Hendrik von (European journal of radiology, 2011)
Purpose - To validate flow measurements within an aortic nickel-titanium (nitinol) stent graft using velocity-encoded cine magnetic resonance imaging (VEC MRI) and to assess intraobserver agreement of repeated flow measurements. - Materials and methods - An elastic tube phantom mimicking the descending aorta was developed with the possibility to insert an aortic nitinol stent graft. Different flow patterns (constant, sinusoidal and pulsatile aortic flow) were applied by a gear pump. A two-dimensional phase-contrast sequence was used to acquire VEC perpendicular cross-sections at six equidistant levels along the phantom. Each acquisition was performed twice with and without stent graft, and each dataset was analysed twice by the same reader. The percental difference of the measured flow volume to the gold standard (pump setting) was defined as the parameter for accuracy. Furthermore, the intraobserver agreement was assessed. - Results - Mean accuracy of flow volume measurements was −0.45±1.63% without stent graft and −0.18±1.45% with stent graft. Slightly lower accuracy was obtained for aortic flow both without (−2.31%) and with (−1.29%) stent graft. Accuracy was neither influenced by the measurement position nor by repeated acquisitions. There was significant intraobserver agreement with an intraclass correlation coefficient of 0.87 (without stent graft, p<0.001) and 0.80 (with stent graft, p<0.001). The coefficient of variance was 0.25% without stent graft and 0.28% with stent graft. - Conclusion - This study demonstrated high accuracy and excellent intraobserver agreement of flow measurements within an aortic nitinol stent graft using VEC MRI. VEC MRI may give new insights into the haemodynamic consequences of endovascular aortic repair.
Available online 2 October 2010
Gesehen am 15.09.2022